Women Participation in Political Affairs During Covid 19: A Study of North East States of India - Dr. Meenu Sharma, (Indian Journal of Social Science and Literature (IJSSL), 2024)
Women have been suffering a lot during the Covid-19 pandemic. Women have faced psychological, social, economic, and political problems during the time of the pandemic. Traditional norms, the natural environment, the economic condition of women, the social system in society, and the education system for women are some of the factors that have been affecting the political participation of women. In 2021, assembly elections were conducted in Assam, West Bengal, Kerala, Tamil Nadu, and Pondicherry. The elections in these states have shown that women's participation in political affairs is more important. The women party workers have participated in all types of party-related activities and election-related tasks, like male party workers, but women's participation in political affairs has decreased due to the burden of other households and caring attitudes towards family members during Covid 19 in the northern states of India. the objectives of this paper are, to analyze the status of women's participation in political affairs during Covid-19 in the North East States of India and to find the reasons for the nonparticipation of women in political affairs during Covid-19. Data was collected through a primary tool structured questionnaire from the sample of 124 women through Google form and telephone interviews, from the four states of the Northeast, states Assam (39), Meghalaya (31), Manipur (29), Arunachal Pradesh (25) of India. 96 (77.42%) of the women respondents have been participating in political discussions, rallies, meetings, and campaigns during elections. 88 (70.97%) of the women respondents have been participating in political affairs by casting their votes during elections. None of the women respondents have formed a political party and contested elections in their state. 96 (77.42%) of the women respondents have an interest in political affairs.